Strategies to Increase After-School Program Staff Skills to Promote Healthy Eating and Physical Activity. Issue 1 (January 2016) - Weaver, R. Glenn; Beets, Michael W.; Beighle, Aaron; Webster, Collin; Huberty, Jennifer; Moore, Justin B.
Standards targeting children's healthy eating and physical activity (HEPA) in after-school programs call for staff to display or refrain from HEPA-promoting or -discouraging behaviors that are linked to children's HEPA. This study evaluated strategies to align staff behaviors with HEPA Standards. Staff at four after-school programs serving approximately 500 children participated in professional development training from January 2012 to May 2013. Site leaders also attended workshops and received technical support during the same time frame. Changes in staff behaviors were evaluated using the System for Observing Staff Promotion of Activity and Nutrition in a pre- (fall 2011) multiple-post (spring 2012, fall 2012, and spring 2013), no–control group study design. A total of 8, 949 scans were completed across the four measurement periods. Of the 19 behaviors measured, 14 changed in the appropriate direction. For example, staff engaging in physical activity with children increased from 27% to 40% of scans and staff eating unhealthy foods decreased from 56% to 14% of days. Ongoing training and technical assistance can have a measureable impact on staff behaviors linked to child-level HEPA outcomes. Future research should explore the feasibility of disseminating ongoing trainings to after-school program staff on a large scale.